The degree of Problem-Solving Strategy Employing in Teaching French from the point of view of Teachers - A Field Study in the Schools of the Basic Teaching (Second Stage) and General Secondary Schools in Latakia City - زريقي, هيام (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research objective is to know the degree of employment of the problem-solving strategy in teaching French from the point of view of teachers in the schools of the second cycle of basic education and general secondary education in Latakia City, and to reveal the differences in the degree of their employment of the problem-solving strategy in teaching French according to the following variables (educational stage, number of years of experience, academic qualification, training courses), and the descriptive analytical approach was relied on. The sample included (128) French language teachers in the schools of the second cycle of basic and secondary education in Latakia City, to which a questionnaire consisting of (38) phrases was applied. The results of the research showed that the research sample members' estimate of the degree of teachers' employment of the problem-solving strategy in teaching the French language from their point of view was average, and the results of the research found that there were no statistically significant differences between the answers of the research sample members about the degree of their employment of the problem-solving strategy according to the variable of the number of years of experience, and the existence of statistically significant differences according to the educational stage variable in favor of the schools of the second cycle of basic education, and according to the scientific qualification variable in favor of teachers with a diploma Educational qualification, depending on the variable of training courses, for the benefit of teachers who have undergone training courses. It also made several recommendations, the most important of which are: the teacher's guide includes a detailed explanation of the steps for applying French language teaching using the problem-solving strategy, and intensifying training courses that support the employment of this strategy in teaching French